Sistem Informasi Geografis Pemetaan Daerah Rawan Pangan Pada Dinas Ketahanan Pangan di Kabupaten Labuhanbatu Utara Dengan Algoritma Dijkstra Berbasis Web - Rico Almanda; Ali Ikhwan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Food security is a strategic aspect that determines community welfare and regional stability. In North Labuhanbatu Regency, 24 out of 82 villages and 8 sub-districts are still categorized as food-insecure. The main challenges include manual mapping processes and difficulties in determining the nearest food distribution routes, which make government interventions less efficient. This study aims to develop a web-based Geographic Information System (GIS) to map food-insecure areas and calculate the fastest distribution routes using Dijkstra’s algorithm. The system was developed using the waterfall model through observation, interviews, and literature studies. The test results show that the system can interactively visualize 24 food-insecure villages and recommend distribution routes with an average distance of 37.04 km and an average travel time of 37.35 minutes. These results are more efficient than manual methods, which tend to generate longer routes and higher travel times. The main contribution of this research is the application of Dijkstra’s algorithm in a web-based GIS for mapping food-insecure villages, which has not been implemented previously in North Labuhanbatu Regency. This finding is expected to support local governments in making strategic decisions regarding the acceleration of food distribution, thereby improving public services and strengthening community food security.